2020
DOI: 10.1111/jonm.13084
|View full text |Cite
|
Sign up to set email alerts
|

Association between work–family conflict and overall well‐being among Chinese nurse leaders

Abstract: Due to the rapid economic development in China, the burden of chronic diseases, such as type 2 diabetes, has skyrocketed at an alarming rate (Hu & Jia, 2018). Together with the emerging ageing population, the growing demands of medical care have posed significant challenges to medical providers in China (Mocan, Tekin, & Zax, 2004). Moreover, China has experienced acute shortages in the number of health care professionals in recent years, especially nurses (Wu, Zhao, & Ye, 2016). In 2013, there were 2.05 nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Work/family conflict occurs when pressures in one role (work/ family) prevent fulfilling demands in the other role (Greenhaus & Beutell, 1985). WFC results in reduced overall well-being (Yu et al, 2020), job satisfaction, lower work commitment and increased burnout/turnover intentions, as well as anxiety, psychological strain, health problems and depression (Amstad et al, 2011).…”
Section: Work/family Conflictmentioning
confidence: 99%
See 1 more Smart Citation
“…Work/family conflict occurs when pressures in one role (work/ family) prevent fulfilling demands in the other role (Greenhaus & Beutell, 1985). WFC results in reduced overall well-being (Yu et al, 2020), job satisfaction, lower work commitment and increased burnout/turnover intentions, as well as anxiety, psychological strain, health problems and depression (Amstad et al, 2011).…”
Section: Work/family Conflictmentioning
confidence: 99%
“…Work/family conflict occurs when pressures in one role (work/family) prevent fulfilling demands in the other role (Greenhaus & Beutell, 1985). WFC results in reduced overall well‐being (Yu et al., 2020), job satisfaction, lower work commitment and increased burnout/turnover intentions, as well as anxiety, psychological strain, health problems and depression (Amstad et al., 2011). COR theory suggests that experienced conflict between work and family domains ties up necessary cognitive, emotional and/or physical resources, thus leaving insufficient resources allocated to work‐related performance.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the high proportion of females in the nurse group (World Health Organization, 2020), they are more influenced by family roles (Yu et al, 2020). Thus, we mainly explore the FWC in this paper.…”
Section: Family-to-work Conflict and Ego Depletionmentioning
confidence: 99%
“…, 2000; Greenhaus and Beutell, 1985). Considering the high proportion of females in the nurse group (World Health Organization, 2020), they are more influenced by family roles (Yu et al. , 2020).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Studies [73] have pointed out that family support can buffer employees' job stress and prevent negative work-related outcomes such as job burnout, and family members have also been shown to provide both instrumental and affective support, which positively affect employee's work life [74]. Medical personnel are no exception; a meta-analysis [75] showed that the con ict between work and family has a strong impact on the high turnover rate of medical personnel, and reducing this con ict can improve their happiness [76]. In addition, communication research [77] has shown that the family as a socialization agent conveys both extrinsic and intrinsic work values for developing a professional identity.…”
Section: Family Support (Fs)mentioning
confidence: 99%